PENGARUH SUHU VULKANISASI DAN KOMPOSISI BENTONITE CLAY YANG DIMODIFIKASI DENGAN ALKANOLAMIDA DARI BAHAN BAKU RBDPKO PADA PRODUK LATEKS KARET ALAM - Friska Erdiana Tambunan; Hamidah Harahap (Talenta Publisher (Universitas Sumatera Utara), 2015)
The is research aims to determine the effect of vulcanization temperature and composition of bentonite clay as good filler on mechanical properties of natural rubber latex product. In this study, we use bentonite clay as filler and alkanolamide as compatibilizer. The material used in this study are high ammonia latex 60%, curative agents such as sulfur, ZnO, ZDEC, AO, KOH, bentonite clay and alkanolamide. Alkanolamide is synthesized from amidation reaction between Refined Bleached Deodorized Palm Kernel Oil and diethanolamine. The methodology includes pre-vulcanizing natural rubber latex with certain formulation, then vulcanized using dipping method. The variable used in this study is filler loading, from 5, 10, 15, 20, and 25 gram, and vulcanization time 10 minutes. The products were then tested in order to observe its mechanical properties, FTIR characterization, SEM characterization and crosslink density. The results show that the synthesized alkanolamide possess the functional group desired. Alkanolamide modified bentonite clay loading is capable of increasing crosslink density and mechanical properties of the products. Optimum filler loading is reported on 10 gram and optimum vulcanization at 120oC.